Utilização da água de coco em pó na preparação de nanopartículas de ferritas - Gonçalves, Nizomar de Sousa (2007)
The present work is dedicated to the studies of the preparation and characterization of the nickel ferrites and cobalt. These ferrites were synthesized by the sun-gel process in suspension of water of coconut lyophilized (ACP) manufactured in Cear´a. This synthesis method allowed to obtain in way efficient ferrite nanoparticles. The samples were treated for 4 hours at 400, 600, 800, 1000 and 1200 C. A preliminary study of the cobalt ferrite varying the concentration of the coconut water above your critical micelle concentration (8,3 mmol/l) it showed as that can influence in the quality of the nanoparticles. The Xray difraction (XRD), the Raman spectroscopy and Scanning Eletron Microscopy (SEM) were applied to study the dependence of the size of the nanoparticle of nickel ferrite with the temperature of the thermal treatment, and the correlation of your electrical properties and the results of M¨ossbauer spectroscopy with your morphologic characteristics. The cristalinity of the ferrites increases with the temperature of the thermal treatment. Measurements of the complex permitivity carried out in cavity resonators at 5,9 and 9,0 GHz have showed that your values of the real part decrease with the increase of the temperature of the thermal treatment (3,6 - 2,4), while the imaginary part stay low for more elevated temperatures of the thermal treatment (about 10−3). Measurements of complex impedance to lower frequencies (75 KHz to 30 MHz), have showed that it increases with the increase of the temperature of the thermal treatment. The results of M¨ossbauer spectroscopy showed that the ferrites presents a structure inverse spinel with the ions Ni2+ occupying the site B and the ions Fe3+ equally distributed in the sites A and and B. To temperatures of thermal treatment below 800 ºC, favored the presence in the grains of a phase Grain Boundary (greater condutivity) observed so much in the behavior of the electric properties as in the answers of the M¨ossbauer spectroscopy.